The Cruise Industry and the Polar Code. Implementing the Polar Code. - Kristiansen, Bendik Skoglund (UiT The Arctic University of Norway, 2019)
The mandatory Polar Code is now set into force with strengthened requirements for vessels operating in polar waters. There are many challenges, and the polar environment adds an increased risk level. The preventive actions towards mitigating risks are more important due to the harsh environment, long distances and limited options for assistant rescue. Most accidents and incidents have pre-occurring causes which are not captured until an unwanted event occurs. A proper reporting regime is essential to identify these causes, and this is done through safety management with all its implications, as well as encouraging a healthy safety culture. Relevant theory is reviewed, and terms and maritime safety challenges are explained to provide the basis for the discussion. Further basis is provided through a survey directed towards polar cruise operators and a root cause analysis of a polar cruise vessel grounding in the Canadian Arctic utilizing reliability engineering methods. The results of the survey and the root cause analysis are discussed related to the maritime safety challenges, and the thesis aims to provide knowledge about the implementation of the Polar Code in the polar cruise shipping segment, and to identify challenges related to this process.